Dhikr therapy training to overcome anxiety in patients with pulmonary tuberculosis - Wachidah Yuniartika; Dawaishafa Diva Nurani; Zuhro Muyassarotus Safaniah (Universitas Muhammadiyah Magelang, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis which spreads through the air and is one of the biggest causes of death in the world. Changes in post-TB conditions, such as weight loss and difficulty in carrying out activities, cause patients to be afraid of their condition. Excessive fear is not balanced with positive thoughts and activities, resulting in psychological stress. The aim of this community service is to apply dhikr therapy to overcome the anxiety of patients suspected of tuberculosis. The implementation of this program is in the form of providing material on the concept of anxiety and dhikr therapy in overcoming anxiety through lectures, videos, questions and answers, giving booklets, and practicing dhikr therapy. This training showed success even though it was not optimal, this was proven by the reduction in anxiety levels of tuberculosis sufferers after being given dhikr therapy. Apart from that, from the observation, tuberculosis sufferers are no longer anxious and more cheerful.